2021
DOI: 10.1111/jbi.14157
|View full text |Cite
|
Sign up to set email alerts
|

Root trait variation of seed plants from China and the primary drivers

Abstract: Aim Root traits play important roles in plant growth and ecosystem processes. Clarifying the primary drivers of variation in root traits is indispensable for understanding and predicting ecosystem responses to environmental changes. Location China. Taxon Seed plant species. Methods We compiled six key first‐order root traits of 437 seed plant species from different biomes, phylogenetic affiliations, plant growth forms and mycorrhizal types in China. The six root traits included root diameter (RD), root tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 102 publications
(216 reference statements)
0
0
1
Order By: Relevance
“…However, we observed that RNC was strongly associated with RCN, whereas RCC was not. This indicated that RNC, rather than RCC, was more important in the trade-offs between C investment and resource uptake in roots (An et al, 2021). Our results is not consistent with the global and regional studies (Kramer-Walter et al, 2016;Wang et al, 2018a;McCormack and Iversen, 2019;Bergmann et al, 2020), we found that the RES explained the most variation of root traits and the trade-off between RD and SRL loaded on the second axis in China, suggesting that root trait covariation may not be generalized from global-scale and other regional analyses.…”
Section: Multidimensional Pattern Of Variation In Root Traitscontrasting
confidence: 92%
“…However, we observed that RNC was strongly associated with RCN, whereas RCC was not. This indicated that RNC, rather than RCC, was more important in the trade-offs between C investment and resource uptake in roots (An et al, 2021). Our results is not consistent with the global and regional studies (Kramer-Walter et al, 2016;Wang et al, 2018a;McCormack and Iversen, 2019;Bergmann et al, 2020), we found that the RES explained the most variation of root traits and the trade-off between RD and SRL loaded on the second axis in China, suggesting that root trait covariation may not be generalized from global-scale and other regional analyses.…”
Section: Multidimensional Pattern Of Variation In Root Traitscontrasting
confidence: 92%